Altered Phenotype of Circulating Dendritic Cells and Regulatory T Cells from Patients with Acute Myocarditis - Paola del Carmen Guerra-de-Blas; Daniela Cruz-González; Elena B. Martínez-Shio; Roberto González-Amaro; Héctor González-Pacheco; Esther Layseca-Espinosa; Carlos D. Escobedo-Uribe; Adriana E. Monsiváis-Urenda (Journal of Immunology Research)
Dendritic cells (DCs) and regulatory T cells (Tregs) play an essential role in myocarditis. However, a particular DC phenotype in this disease has not been assessed. Herein, we aim to evaluate myeloid (mDCs) and plasmacytoid DC (pDC) phenotype, as well as Treg levels from myocarditis patients and healthy controls. Using multiparametric flow cytometry, we evaluated the levels of myeloid DCs (mDCs), plasmacytoid DCs (pDCs), and Tregs in peripheral blood from myocarditis patients (n=16) and healthy volunteers (n=16) and performed correlation analysis with clinical parameters through Sperman test. DCs from myocarditis patients showed a higher expression of costimulatory molecules while a diminished expression of the inhibitory receptors, ILT2 and ILT4. Even more, Treg cells from myocarditis patients displayed higher levels of FOXP3 compared to controls. Clinically, the increased levels of mDCs and their higher expression of costimulatory molecules correlate with a worse myocardial function, higher levels of acute phase reactants, and higher cardiac enzymes. This study shows an activating phenotype of circulating DCs from myocarditis patients. This proinflammatory status may contribute to the pathogenesis and immune deregulation in acute myocarditis.